Strand 2: Physical Universities Can Apply Virtual Technologies too: The Use of Networked Technologies to Support Collaborative Learning - Holtham, Clive; Tiwari, Ashok (Proceedings of the International Conference on Networked Learning, 1998)
There has been an extensive use of networked technologies to support learning by post-graduates, particularly MBA students (Wheeler and Krapfel, 1996). There appears by contrast to have been relatively less application of such technologies to support undergraduate students. This paper reports on the application of an innovative computer supported collaborative learning methodology in parallel in two universities. It draws on this empirical work to examine the implications at institutional level for a greater use of such networked technologies that have also been strongly advocated for use by 'virtual universities'.